Electromigration failure mechanisms of 〈111〉 -oriented nanotwinned Cu redistribution lines with polyimide capping - I-Hsin Tseng; Po-Ning Hsu; Tien-Lin Lu; K.N. Tu; Chih Chen (Results in Physics, 2021)
Electromigration (EM) mechanisms are well studied in damascene copper lines capped with inorganic dielectrics. However, EM in Cu redistribution lines (RDLs) capped by organic layers is not well-understood. In this study, nanotwinned copper (nt-Cu) is adopted, which has high mechanical strength as well as excellent electrical resistivity. We designed EM test vehicles with four-point probes to measure the lifetime of RDLs and examine the failure mechanisms of the Cu RDLs. The length of the RDLs was 800 µm, the width was 10 µm, and the height was 5 µm. The samples were tested at 200 °C, with current densities of 1.0 × 106 A/cm2. The results indicated that there were two main failure mechanisms, including EM-induced voiding and oxidation of Cu RDLs. The measured EM lifetime of nt-Cu RDLs is 4 times longer than that of regular Cu RDLs.